Determinants of Students’ Academic Achievement: A Structural Equation Modelling Approach - Nor Hasnida Md Ghazali; Mahizer Hamzah; Syaza Hazwani Zaini; Noor Insyirah Abu Bakar; Nor Azlin Mohd Rusdin (An Overview of Literature, Language and Education Research Vol. 5, 2024)
The use of e-learning and online assessment has grown exponentially in the educational sector worldwide. Two factors could influence academic performance include e-learning practices and competency in assessing. In Malaysia, the use of e-learning is still new compared to Western countries and other developed countries. The main purpose of this study is to explore the degree of influence of e-learning practices and competency in assessment on the academic achievement of students. This study is using a quantitative approach. The study method is the survey method. The population of the study involves student teachers from the three selected universities in Selangor and Perak. Sample selection is made using a random sampling technique. 460 student teachers are selected. The questionnaire for e-learning practices is adapted from OLES [1] and the competency in assessment comes from Zahari [2]. The structural equation modelling (SEM) analysis is used to test the hypothesized relationship. The results show that e-learning practices, knowledge and skills in assessing and attitude in assessment significantly influence the academic achievement of students. E-learning practices have the highest value and a significant standardized regression coefficient with students’ achievement (0.39) followed by skills in assessment (0.27), knowledge in assessment (0.09) and lastly attitude in assessment (0.08). This study contributes to the understanding of the contribution of those factors toward students’ academic achievement especially in the era of the pandemic. In conclusion, the results show that e-learning practices (E-L), knowledge on assessment (KA), skills in assessing (SA) and attitude in assessing (AS) would significantly and positively influence the students’ academic performance. So, further research is needed to compare with students from private universities for more rigorous results. Those from private universities might have more convenience in terms of internet usage and accessibility to materials. The core findings of the study have a few implications for higher education and practice, measurement and theory development, and future research. It is suggested that qualitative studies be conducted in future research to go in-depth about these matters.